2018
DOI: 10.1073/pnas.1803975115
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystalline bacterial outer membranes are critical for antibiotic susceptibility

Abstract: The outer membrane (OM) of Gram-negative bacteria is a robust, impermeable, asymmetric bilayer of outer lipopolysaccharides (LPSs) and inner phospholipids containing selective pore proteins which confer on it the properties of a molecular sieve. This structure severely limits the variety of antibiotic molecules effective against Gram-negative pathogens and, as antibiotic resistance has increased, so has the need to solve the OM permeability problem. Polymyxin B (PmB) represents those rare antibiotics which act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 59 publications
5
91
0
1
Order By: Relevance
“…The OM is made up of a unique asymmetrical lipid bilayer, with the inner leaflet consisting of phospholipids and the outer leaflet composed by lipopolysaccharide. The OM can act as a barrier to prevent drugs from reaching intracellular targets, rendering the Gram‐ E. coli presents a relatively high resistance to minocycline . Nevertheless, it is reported that the OM is sensitive to ROS .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OM is made up of a unique asymmetrical lipid bilayer, with the inner leaflet consisting of phospholipids and the outer leaflet composed by lipopolysaccharide. The OM can act as a barrier to prevent drugs from reaching intracellular targets, rendering the Gram‐ E. coli presents a relatively high resistance to minocycline . Nevertheless, it is reported that the OM is sensitive to ROS .…”
Section: Resultsmentioning
confidence: 99%
“…Unlike Gram+ species, Gram‐ bacteria lack the thick peptidoglycan cell wall; instead, they possess an additional outer membrane (OM). Most antibiotics can hardly pass through the hydrophobic OM, resulting in their little inhibition effect to Gram‐ bacteria . Therefore, destroying the OM is an effective way to help antibiotics kill Gram‐ bacteria and acquire broad‐spectrum antibacterial abilities .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, simulations demonstrate that models with protonated lipid A form more compact bilayers, which may represent a better match to the liquid-crystalline phase the outer membrane is believed to adopt physiologically. 5,67 Determination of the physiologically-relevant lipid A phosphate charge representation is a crucial problem that simulations need to address, especially in light of these differences observed between simulations with protonated or deprotonated lipid A phosphate groups.…”
Section: Discussionmentioning
confidence: 99%
“…OM model membranes were constructed using an inner leaflet of phospholipids and an outer leaflet of LPS without O-antigen. These were made and deposited directly onto silicon or onto lipid-coated gold surfaces (2)(3)(4)(5). The former produces membranes that are essentially in contact with the substrate, whereas the latter produces asymmetric membranes that float $15 Å above the solid support, reducing the frictional influence of the support on the membrane and making these biomimetics suitable for biophysical and structural studies using neutron reflectometry (NR).…”
Section: Introductionmentioning
confidence: 99%